STRATEGI PENGEMBANGAN PALA (MYRISTICA FRAGAN HAITT) DI KECAMATAN TANJUNG RAYA KABUPATEN AGAM (STUDI KASUS : KELOMPOK TANI SABIK TAJAM NAGARI TANJUNG SANI) - Analia, Devi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
The study aims to analyze development strategy of nutmeg (Myristic fragan haitt) in Tanjung Raya Sub-district, Agam District. The study applied decriptive method. The data were collected through in depth interview with three internal key infromants, in this case farmers, and external key informants including head of forestry and plantation department of Agam District, and one nutmeg farmer. SWOT analysis were applied to formulate development strategy of nutmeg at Sabik Tajam farmers group in Tanjung Raya Sub-district, Agam District. The development strategies include developing cooperation with government and private sector; technology improvement for value added of nutmeg farmers income through nutmeg agro-industry; promotion of nutmeg sector by the government, both in local and international market; participating in training held by relevant government authorities particularly those related to nutmeg processing and establishing house of HPT (plant pests and disease) to overcome the pests and disease; conducting training to the farmers covering the marketing aspect; cultivation and technology development; the involvement of UPTD (technical implementation unit at local) in cultivation and HPT of nutmeg; optimizing the resources and marketing, and develop cooperation with the farmers group that have more advanced technology.